2008
DOI: 10.1177/1049732308315108
|View full text |Cite
|
Sign up to set email alerts
|

Exploring One's Own Human Condition: Adults Affected by Cystic Fibrosis

Abstract: Drawing on a sample of 11 interviews in France with adults affected by cystic fibrosis, and applying grounded-theory analysis, I describe illness-related learning processes in the case of persons affected by a genetic disorder with early onset. Three outcomes might be of interest to health professionals. First, the diagnosis of genetic disease does not imply that the patients consider themselves to be ill. The meaning of being affected by a genetic disorder has to be understood. Second, these patients gain a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Admi (1996) also found that young people with CF strive to define themselves as normal and do not dwell on death until negative events force the body into stark relief and threaten normalcy. Huyard (2008) underscored similar findings in adults with CF. If the patient has no symptoms at the time of diagnosis, the disease's label is rendered irrelevant and normalcy is not compromised.…”
Section: Review Of the Literaturesupporting
confidence: 70%
“…Admi (1996) also found that young people with CF strive to define themselves as normal and do not dwell on death until negative events force the body into stark relief and threaten normalcy. Huyard (2008) underscored similar findings in adults with CF. If the patient has no symptoms at the time of diagnosis, the disease's label is rendered irrelevant and normalcy is not compromised.…”
Section: Review Of the Literaturesupporting
confidence: 70%
“…She found that youth with complex healthcare needs described multiple transitions that occurred simultaneously as they moved to adult-oriented services, including the need to reestablish trust in providers, assume responsibility for self-management activities in multiple realms, and learn to navigate within an adult culture where expectations were uncertain and less parent-centered. Huyard 14(pp540) interviewed adults with Cystic Fibrosis and found that they had gradually experienced a “critical internalization”, in which they learned how to manage their illness, accepting or rejecting medical advice based on their responses, and concluding that having a genetic condition was not the same as being ill.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge and understanding developed gradually as an accumulation of learning over time, as described previously . Families, the CF team and peers with CF played important roles in informing participants learning.…”
Section: Discussionmentioning
confidence: 87%
“…Previous research has explored adults experience of living with CF , although not specifically in relation to the gut. Where this has been carried out in other chronic GI‐related conditions, patients’ perspectives have helped inform clinicians understanding and practice .…”
Section: Introductionmentioning
confidence: 99%